2015
DOI: 10.1111/cob.12103
|View full text |Cite
|
Sign up to set email alerts
|

The effects of physical activity interventions on preventing weight gain and the effects on body composition in young adults with intellectual disabilities: systematic review and meta‐analysis of randomized controlled trials

Abstract: Summary The aim of this study was to examine the literature on randomized controlled trials examining the efficacy of physical activity interventions to prevent weight gain and the effects on body composition in young adults with intellectual disabilities.A systematic search of Medline, Emabse, CINHAL, PsychINFO, Cochrane library and ERIC was conducted from 1946 to September 2014. Eligibility criteria included; randomized controlled trials of a physical activity intervention: objective measure of body weight a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 54 publications
(100 reference statements)
1
27
0
Order By: Relevance
“…Previous research clearly documents that this service user group tends to be even less active than the general population (Emerson, ; Finlayson et al ., ). A recent systematic review highlighted the need for research that considers the barriers that may prevent service users with intellectual disabilities taking part in regular physical activity (Harris et al ., ). This study offers a preliminary understanding of three barriers that hindered increasing activity levels: (i) acceptance of current levels of inactivity, (ii) rendering physical activity a low priority compared to other activities both in timetabling and in resource allocation, and (iii) issues regarding communication and the appropriate format for physical activity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous research clearly documents that this service user group tends to be even less active than the general population (Emerson, ; Finlayson et al ., ). A recent systematic review highlighted the need for research that considers the barriers that may prevent service users with intellectual disabilities taking part in regular physical activity (Harris et al ., ). This study offers a preliminary understanding of three barriers that hindered increasing activity levels: (i) acceptance of current levels of inactivity, (ii) rendering physical activity a low priority compared to other activities both in timetabling and in resource allocation, and (iii) issues regarding communication and the appropriate format for physical activity.…”
Section: Discussionmentioning
confidence: 97%
“…Family carers were predominantly older adults caring for their adult offspring, so they did not feel able to take the lead on promoting physical activity in the family. Nor did it help that the service users were obese, for obesity limits people's physical abilities (Finlayson et al ., ; Harris et al ., ; Murray, ). The view of physical activity as a special task that required special arrangements mirrors other findings that participants considered a healthy diet to involve going on a diet which necessitated eating special foods and avoiding other foods (Cartwright et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…While physical activity is considered important for weight management in the general population, there is limited literature to suggest that increased physical activity will help to reduce weight in adults with IDD. A recent review by Harris et al () indicates that physical activity interventions did not significantly change body weight or BMI in young adults with IDD. Possible explanations for the limited effects of physical activity interventions could be attributed to the ‘dose’ of physical activity prescribed in some interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity is considered an important strategy to promote weight loss because of its pivotal role in energy balance and the regulation of body weight through increased energy expenditure (Donnelly et al 2009;Harris et al 2015). However, adults with IDDs are less physically active than the general population (Rimmer et al 1995;Rimmer et al 2004;Melville et al 2007a;Spanos et al 2013;Harris et al 2015). A review by Melville et al (2007b) found that only 8-16% of adults with IDD met criteria for a physically active lifestyle, compared with 20-37% of the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents with intellectual disability are also less likely than other children to have someone with whom to do physical activity, and more likely to perceive that physical activities are too hard to learn 50 . Future studies should take into account these multiple barriers and aim to overcome the difficulties people with intellectual disability experience in participating in physical activity 51 .…”
Section: Discussionmentioning
confidence: 99%